Domestic violence subjected to different patterns of cultural marriage - Boujarian, Nazanin; Ninggal, Mohd Tajuddin; Ssekamanya, Siraje Abdallah; Noroozi, Masood (Scientific Research Publishing, 2016)
Violence against women and girls and its legal, social, psychological and related issues are not a new topic in social science. However, it has attracted a significant amount of attention from many researchers and still needs further investigation. Among different sources provoking violence against females such as gender inequality, insufficient protective legal systems, cultural pressure and etc., different marital patterns have been reported by the informants of this research. Child marriage, consanguineous marriage and unregistered/white marriage put girls and women in a vulnerable position. For example, under the pressure of abusive behavior in family, females escape from patriarchal family, leave their city/country and live as a refugee. In more severe cases, they attempt suicide under the pressure of pain and suffering. In comparison with developed countries where the human rights of the female are well-established and such marital patterns are not seen, these types of martial patterns are reported in patriarchal societies. Therefore, this study introduces these patterns and describes their effects on provoking the domestic violence. Through interview sessions with victims of domestic violence, a qualitative methodology was used to gain in-depth information. To avoid or reduce the financial, emotional and physical costs of domestic violence, it is necessary that counselors, health care provider systems, society and authorities prioritize prevention methods and intervention programs to improve the cultural level of the society and to encourage people toward developing a violence-free society